Pertimbangan Hakim dalam Perkara Peredaran Uang Palsu di Pengadilan Negeri Limboto - Santika Tuadingo; Suwitno Suwitno; Julisa Aprilia Kaluku (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
This journal discusses the judge's considerations in the case of circulating counterfeit money at the Limboto District Court. By using normative research methods and statutory approaches and case approaches. Counterfeiting currency is considered a violation that can harm the interests of society. The case being studied is the decision of the Limboto District Court Number 119/Pid.B/2022/PN Lbo, where two defendants with the initials DT and CAL were found not guilty of the crime of forgery and circulation of counterfeit money. Even though the public prosecutor had presented evidence and witnesses, the judge acquitted the defendant because there was a discrepancy between the evidence presented and the counterfeit money distributed by the defendant.